Persepsi Guru PPG terhadap Integrasi TPACK dalam Pembelajaran Bahasa Indonesia - Sari, Dewi Ratna; Sujinah, Sujinah; Fatin, Idhoofiyatul (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The focus of this research is to determine PPG teachers' perceptions of the integration of TPACK in Indonesian language learning. There are seven known components in TPACK that must be mastered by teachers, namely CK (Content Knowledge), TK (Technological Knowledge), PK (Pedagogical Knowledge), PCK (Pedagogical Content Knowledge), TCK (Technological Content Knowledge), TPK (Technological Pedagogical Knowledge) and TPACK (Technological Pedagogical Content Knowledge). The data collection technique was through a closed questionnaire with a sample size of 30 PPG Daljab category 1 class 3 teachers. Researchers used a Likert scale in their research with intervals of 1-4. Research data was analyzed using quantitative analysis. The results of this research are displayed through percentages. The results of the research conducted show that PPG teachers have a good perception of the implementation of TPACK in Indonesian language learning. The CK component is 82% in the very good category, the TK component is 76% in the good category, the PK component is 79% in the good category, the PCK component is 79% in the good category, the TCK component is 70% in the good category, the TPK component is 78 % in the good category, and the TPACK component is 74% in the good category.